Menelisik Pentingnya Penerapan Manajemen Usaha Bagi UMKM Dalam Persaingan di Era Digital - Suharto; Intan Damawati; Lulu Febriany (Universitas Gajah Putih, 2026)
The development of digital technology has driven significant transformations in the management of Micro, Small, and Medium Enterprises (MSMEs), particularly in marketing, operations, and finance. Although digitalization opens up significant opportunities for increased competitiveness, its implementation still faces various obstacles such as low digital literacy, limited resources, and infrastructure inequality. This study aims to analyze the importance of business management implementation in supporting the success of MSMEs in the digital era. The method used is a descriptive qualitative approach using a literature review technique from various current literature sources. The results of the study indicate that the success of digital transformation is determined not only by the ability to adopt technology but also by the ability to integrate technology into an effective business management system. Without good management, digitalization tends to have no significant impact on business performance. Therefore, strengthening managerial capacity is key to increasing the competitiveness and sustainability of MSMEs in the digital era.